DEREK WALLCOT’S A FAR CRY FROM AFRICA: SEMANTICANALYSIS - NATHANIEL G. GIDO; CANOY, PRISCILLA F.; JOSE GILA; EMELITA POSTRERO; SULPICIA VILLACERAN; JANELA SUGALA (International Journal of Multidisciplinary Research and Studies, 2022)
The Caribbean culture is the main theme in the works of West Indian poet and playwright Derek Walcott, whose full name is Derek Alton Walcott. The poem also talks about the bloodshed in Kenya and the speaker's own split identities as a result of colonialism. The speaker of the poem, who is connected to both England and Africa, struggles with how to interpret the violence of the battle. Understanding the poet's multiple literary techniques can help us comprehend the poem more clearly. It matters how the poet portrays both colonists and indigenous people. The poem's conclusion lines, which offer a number of questions, imply that the author is indeed not willing to solve the issues. The poem's significance and congruence with the earlier-mentioned context are due to the symbols and images that were explored.